Integration of Local Values and Religious Moderation in Civic Education to Enhance Social Tolerance at SDN 01 Banjar Sari, Baradatu District - Suryadi (STIS Sultan Fatah, 2026)
This study is motivated by the suboptimal internalization of social tolerance values in Civic Education (PKn), despite their normative inclusion in national education objectives. This gap indicates that value integration in learning remains largely symbolic and has not been transformed into meaningful learning experiences. This study aims to analyze the integration of local values and religious moderation in PKn learning and examine its influence on students’ social tolerance attitudes at SDN 01 Banjar Sari, Baradatu District. A qualitative approach with a case study design was employed. The research subjects included the principal, Civic Education teacher, and students of grades IV, V, and VI. Data were collected through observation, in-depth interviews, and documentation, and analyzed using an interactive model. The findings reveal that the integration of local values and religious moderation has not been systematically designed in lesson planning and implementation, resulting in implicit and normative practices. Consequently, the improvement of students’ social tolerance remains limited and has not reached a stable level of internalization. This study highlights that the effectiveness of tolerance education depends on the ability of learning processes to construct values into contextual, participatory, and reflective social experiences. Therefore, this research contributes by emphasizing the importance of a transformative pedagogical approach in integrating local values and religious moderation in Civic Education.